Advocate and Survivor Perspectives on the Role of Technology in Help Seeking and Services with Emerging Adults in Higher Education - Voth Schrag, Rachel (Journal of family violence, 2022)
Emerging adults, aged 18-25, have come of age in a technology oriented world. The internet has been critical in mediating their personal relationships and their understanding of daily life. Emerging adults are also at unique risk of experiencing intimate partner and sexual violence (IPV & SV) Given the increasing infusion of information communication technology (ICT) into anti-violence advocacy, and the broad use of ICT among college-attending emerging adults, this study aimed to explore how both survivors and advocates are leveraging technology for support. Using a QUAL + qual methodology (Morse and Niehaus, 2009), data were collected as part of an evaluation of campus-based advocacy as implemented in five programs. Interviews took place with 23 campus and community-based advocates, and 25 survivors of interpersonal violence who had accessed campus-based advocacy services. Additionally, 63 survivors who engaged in campus-based advocacy services responded to an online survey. Key domains identified were: 1) technology as a means of informing potential clients about services; 2) the role of technology in help-seeking, including its role in tailoring and extending the reach of services; and 3) the importance of recognizing technology facilitated abuse in the advocacy and education process with emerging adults. As advocacy programs are rapidly shifting to technology facilitated services in the wake of COVID-19, this study provides data on advocate and survivor experiences with technology, which can inform these changes across the spectrum of IPV & SV services.